(untitled) - Ladousse, Gillian Porter (Oxford, 1995)
This book helps students to become more aware of the different strategies used in reading. The units are arrangedthematically, with a variety of texts that include excerpts from books, newspaper and magazine articles, afable, a short story and a short play.
Keywords: english language,english language,Tiếng Anh,Tiếng Anh; study and teaching,reading,textbooks for foreign speakers,Dạy và học,Kỹ năng đọc,Giáo trình dành cho người nước ngoài